Martyn Rady, Habsburgii. Ambiția de a stăpâni lumea [The Habsburgs. The ambition to rule the world], transl. Lia Decei (București: Corint, 2023), 592 pages - SUĂTEAN, Ovidiu Cristian (Studia Universitatis Babeș-Bolyai Historia, 2025)
A fundamental question for any new work is: what does it truly add to the existing historiography? This question may have been the starting point for Martyn Rady in his project, which resulted in the work titled The Habsburgs. To Rule the World, published in 2020. It was translated into in Romanian under the title Habsburgii. Ambiția de a stăpâni lumea,[1] published in 2023. The history of the Habsburgs has been the subject of substantial monographs in terms of both volume and quality; to name but a few: R.J.W. Evans, A.J.P. Taylor, Jean Berenger, Charles. W. Ingrao, Jean des Cars, or the synthesis of the Austrian Academy of Sciences. Accordingly, at first glance, considering the qualitative and quantitative consistency of earlier scholarship, Martyn Rady’s work could appear redundant within Habsburg historiography. [1] The original version: Martyn Rady, The Habsburgs. To Rule the World (New York: Basic Books, 2020), 416 pages.